Dynamic response of wind energy conversion systems under various faults. (10th April 2015) - Talebi, Nasser; Sadrnia, Mohammad Ali; Darabi, Ahmad
One of the most important features of energy generation sources is robustness of their structure against faults. Wind energy conversion systems (WECSs) are generally subjected to occurrence of various faults. Many modelling techniques which have been already introduced for the modelling of the faults or observing the influences of the faults cannot be considered wide–ranging to include any fault at any point of the WECS. On the other hand, for the purpose to explore the impacts of faults on several components of the WECS and probably improving the future design of it, a type of model is required in which mechanical and electrical parts are modelled properly with some details. In this paper, a comprehensive dynamic model for the WECS is presented by which a variety of faults such as sensors, actuators and power grid faults can be studied and effects of these faults on voltage, current and other signals of the WECS can be investigated. In addition, the dynamic model described by this paper can be applied simply to design the fault detection, fault tolerant control and protection systems of the WECS.